The effect of percentage of water, salt and acidity of butter to its keeping qualities - Nystrom, Amer B. (My University, 1907)
Introduction: With the advance of civilization there seems to be an increase in the demand for more fancy as well as more wholesome articles of food. This is not only in the line of delicacies but in staple articles as well. This increase in demand is very marked in the products of the dairy and creamery. Milk has been a very important article of food for ages back, but it was almost solely used as a beverage, and no attempt was made to find its composition or to learn what could be made of it. Butter, as we all know is made from the fat in milk. It is one of the oldest of foods. Even as far back as 2000 years B. C. we learn that the Hindoos were interested in cattle raising and valued their cows according to their yeild of butter. We know nothing of the quality of the butter made at that time, however,expect that it must have contained about as much casein as fat, judging from the Greek derivation of the word "butter" which means, cow cheese. Butter was first used as an ointment for injuries to the skin, later it was used to enrich cooked foods, and only the rich could afford to use it. It was seldom eaten fresh, the common practice was to melt it and store it underground, leaving it there for years, sometimes as long as a half century. Butter -making as we know it today has been in practice for a number of generations, but it has been only within the last twenty years that any attempt has been made to improve the product or make investigations concerning it. Even with the advanced learning on the dairy line, that we have today, there are many points that we are not clear on or indeed know nothing about. We know that bacteria…
Citation: Nystrom, Amer B. The effect of percentage of water, salt and acidity of butter to its keeping qualities. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Composition of Food; Food Preservatives; Food Quality; Butter; Dairy Products; Theses